Decidualisation and placentation defects are a major cause of age-related reproductive decline - Laura Woods (Nature Portfolio, 2017)
Advanced maternal age has been associated with lower reproductive success and higher risk of pregnancy complications. Here the authors show that maternal ageing-related embryonic abnormalities in mouse are caused by decidualisation and placentation defects that can be rescued by transferring the embryo from an old to a young uterus.